Sanksi Pidana terhadap Pelaku Pengeroyokan yang Menyebabkan Kematian (Putusan Nomor 399/Pid.B/2020/PN Dps) - Putu Kayla Yunita Dewi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
Beating is an act that causes someone to be physically injured on purpose, with that there is a need for legal protection for victims of beatings because it is very disturbing to the community. This is regulated in the Criminal Codebook II chapter V. The purpose of this research is to discuss the regulation of the criminal act of beating that causes death and to examine the judge's considerations in imposing criminal sanctions on perpetrators who kill by beating according to Judge's Decision Number 399/Pid.B/2020 /PN Dps. This research is normative research with a statutory and conceptual approach. Primary legal sources, namely legal materials in the form of legislation, namely: the Criminal Code, and Legal Decisions. Secondary legal sources, namely official legal materials that support previous materials in the form of literature, books, and scientific journals. The technique used in making this research uses the collection of document research materials, including existing legal arrangements. existing regulations, self-defense by taking vigilante freely is carried out arbitrarily without any sense of guilt. Meanwhile, the beatings are also related to Article 170 of the Criminal Code. The suggestion is that the Denpasar District Court provides confirmations for each decision issued by the judge so that criminal sanctions are in accordance with applicable regulations and so that in the future there will be no injustice created over cases that have been resolved and it is hoped that in the future the community will be wiser and it would be better if the public could report similar cases to the competent authorities (law enforcement officers), in order to protect and ensure legal certainty in the community.